Mechanisms of removal of heavy metal ions by ZnO particles - Le, Anh Thi; Pung, Swee-Yong; Sreekantan, Srimala; Matsuda, Atsunori; Huynh, Dai Phu (Heliyon, 2019)
Effluent discharges from industry and domestic waste containing unknown inorganic pollutants. In this work, different mechanisms of heavy metal ions removal using ZnO particles were studied. ZnO particles were synthesized using solid precipitation technique. The morphology of ZnO particles was rod-like shape. The average length and diameter of ZnO particle were 497.34 ± 15.55 and 75.78 ± 10.39nm, respectively. These particles removed effectively heavy metal ions such as Cu(II), Ag(I) and Pb(II) ions with efficiency >85% under exposure of 1 hour of UV light. However, poor removal efficiency, i.e. <15% was observed for Cr(VI), Mn(II), Cd(II) and Ni(II) ions. The removal of these heavy metal ions was in the forms of metals or metal oxide via reduction/oxidation or adsorption mechanism.